Ekstrak Tempe Kedelai Hitam dan Ubi Jalar Ungu Terhadap Toleransi Darah Tikus Model DMT2 - Ayu Wulansari, Mustika; Rahayu Lestari, Sri; Gofur, Abdul (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Diabetes mellitus type 2 (DMT2) is caused by the ineffective use of insulin by the body. DMT2 with hyperglycemia causes circulatory system disorders, such as intracellular ion imbalance that causing changes in cell size and cell membrane fragility. Soybean black tempe and purple sweet potato have a potential therapy for patients with DMT2. This study aims to determine the blood osmotic tolerance of rat model DMT2 treated by the mixture of black soybean tempe extract and purple sweet potato. Osmotic tolerance is indicated by the level of erythrocyte membranes damage, i.e. crenation and hemolysis. The results showed that chemical compounds such as glibenclamide works better to lowers damaging of the cell membrane as compared to treatment of a mixture of natural compounds soybean black tempe and purple sweet potato.